Listening with young children: enchanted animism of trees, rocks, clouds (and other things) - Merewether, Jane (2018)
This article introduces the notion of enchanted animism, contending that an enchanted re-animation of the world may be necessary for learning to live on a damaged planet. The paper draws on a project with young children which invited them to share what they thought was ‘good’ in the outdoor spaces at their early learning centre. These encounters revealed children’s relationship with nonhuman elements which seemed to be calling in and enchanting children. In particular, children’s playful animation of so-called inanimate things – trees, rocks, clouds – allowed an egalitarian view of the world in which both humans and nonhumans were seen to be engaged in intentional projects. The paper argues that enchanted animism kindles children’s sensitivity to Earthly processes, enabling them to listen to the Earth more attentively, with the awareness and responsiveness that a planetary crisis demands.